Insectophilia play zone - Mohd Yunos, Mohd Yazid; Mohamed, Noorizan; Abdul Aziz, Nor Juliana (Universiti Putra Malaysia Press, 2013)
As Malaysia is nature rich-filled with a myriad of insects, that comprise hundreds of thousands of species, and with more species yet to be found, there is the potential to be explored through children play area. The proposed insect-loving children play area will experience firsthand how the metamorphosis of insects such as beetles, flying butterflies, dragonflies, damselflies, moths, beetles, crickets, grasshoppers take place right before the children's eyes.